Revisiting nephrocalcinosis: A single‐centre perspective. A northern Italian experience. Issue 2 (February 2016) - Piccoli, Giorgina Barbara; De Pascale, Agostino; Randone, Olga; Vigotti, Federica Neve; Priola, Adriano Massimiliano; Naretto, Carla; Ferraresi, Martina; Aroasio, Emiliano; Gonella, Silvana; Mongilardi, Elena; Scognamiglio, Stefania; Consiglio, Valentina; et al.
Abstract: Aim: Nephrocalcinosis is a clinical‐pathological entity characterized by the deposition of calcium salts within the kidney parenchyma. Both the protean presentation and multiple causes may explain the lack of data regarding its prevalence. The aim of this study is to report the prevalence and main clinical features of nephrocalcinosis diagnosed in a newly opened nephrology outpatient unit. Methods: Analysis on the data we prospectively gathered from the start of activity (2007–2013) was carried out. Clinical and laboratory data were collected from the medical records and from the general laboratory; diagnosis was based upon imaging data reviewed by the same radiologists. Results: Sixty‐five of 2695 patients referred to our unit were diagnosed with nephrocalcinosis (2.4%). The affected patients were younger than the overall out‐patient population (median: 37.7 (min–max: 8–82) vs 63 years (2–102) P < 0.001), with higher female prevalence (68% vs 51.4%: P < 0.05) and better preserved kidney function (CKD‐EPI 103 (23–165) vs 60 mL/min (3.2–169) P < 0.001). Kidney stones were the main reason for referral (35.4%), followed by electrolyte disturbances (22.7%), acute pyelonephritis (4.6%), AKI or CKD (4.6%). Nephrocalcinosis was associated with autoimmune diseases in 29% and with microcythaemia in 23%, while positive family history was present in 23% of patients. Various electrolyte disturbances were observed, with hypercalciuria being the hallmark of beta thalassaemic patients. Conclusions: Nephrocalcinosis is a rare, but not exceptional disease in nephrology. In Mediterranean countries, microcythaemia would appear to be a major cause of this disease. Greater awareness of nephrocalcinosis is needed for an integrated approach involving various branches of internal medicine and radiology. Summary at a Glance: Piccoli et al . have reported the prevalence and main clinical features of nephrocalcinosis diagnosed in a newly opened nephrology outpatient unit and found that nephrocalcinosis is rare. Microcythaemia might be a major cause of the disease in Mediteranean countries.